The effect of two models from the learning cycle on the achievement of second grade students Intermediate in chemistry (Journal of the College of Basic Education, 2022)
The problem of the current research was identified in answering the following question:- What is the effect of the three-stage learning cycle model and the five-stage model on the achievement of second-grade intermediate students? The research aims to know the effect of two models of the learning cycle on the achievement of second-grade intermediate students in chemistry.1- There is no statistically significant difference at the level (0.05) between the average scores of the students of the first experimental group who study according to the three-stage learning cycle model and between the average scores of the students of the second experimental group who study according to the five-stage learning cycle model and between the average scores of the students of the control group Which is taught according to the usual method of collection.The experimental method with partial control and with a post-test for achievement was chosen. The research was applied to the students of the second intermediate grade in the Khadija Al-Kubra Intermediate School of the General Directorate of Education in Baghdad / Al-Karkh Third. The research was rewarded with some variables. The research experiment was applied at the beginning of the first semester of the academic year (2007/2008). After completing the experiment, the achievement test was applied to the students of the research sample, and after correcting the students’ answers and treating them statistically by using one-way analysis of variance and Scheffe’s test for comparisons, the following results were reached. The two experimental groups outperformed the control group in achievement. In light of the results, the researchers concluded that the adoption of two models of the learning cycle (three and five) has a positive effect on the achievement of the second intermediate grade students in chemistry. Using the learning cycle model for students of different grades and for different study subjects.